100-W-class superconducting transmit bandpass filter using thick disk resonator made with Gd–Ba–Cu–O single-crystal bulk. (5th March 2015) - Saito, Atsushi; Tsurui, Ryota; Kato, Tomoki; Nakajima, Kensuke; Teshima, Hidekazu; Ohshima, Shigetoshi
Abstract: A 100-W-class superconducting bandpass filter (BPF) with a center frequency of around 5 GHz and a bandwidth of 100 MHz was successfully fabricated using thick disk resonators made with GdBa2 Cu3 O y (GdBCO) single-crystal bulk. We designed a five-pole BPF and analyzed the frequency responses and electromagnetic fields. The five-pole BPF optimized by simulation was made from GdBCO superconducting bulk resonators and five pairs of Al2 O3 substrates in a Cu cavity with trimming mechanisms. Its filtering with low insertion loss was clearly evident at around 30 K, and it could handle more than 100 W.